Household Water Security Index: development and application in the Awash Basin of Ethiopia. Issue 2 (3rd April 2022) - Hailu, Reta; Tolossa, Degefa; Alemu, Getnet
ABSTRACT: Despite water security becomes a complex global challenge; its assessments are spatially and temporally inconsistent. This affected water security monitoring at the local level. Some studies attempted to downscale national, regional or global level indicators to local scale, which have several shortcomings. Therefore, this study came up with a new Household Water Security Index to estimate the state of water security at a local level. The study constructed Household Water Security Index (HWSI) based on water resources availability (R), access (A), utilization (U), capacity (C), and environment (E), and water institution (I) indicators. It also tested the index using a sample district in the Awash Basin of Ethiopia. A cross-sectional firsthand data were collected from randomly selected 400 households. A multivariate technique called Principal Component Analysis (PCA) and bivariate correlation were employed. The result revealed that every household is either chronically or transitionally water unsecured. This was mainly due to poorly organized institutions, as well as lack of both the system and knowledge of water management systems under scarcity and surfeit. In some areas, there are moderate resource constraints. In other areas, the capacity to use water is very low. Yet the institutional performance was consistently weak. We concluded that first; macro-level indicators often obscure the local realities. Thus, the policy-makers and development planners need to prioritize the household's situations accordingly. Second, water resources availability with proper use and capacity plays a pivotal role to achieve household water security. Third, it is important to integrate institutional elements in water security as a mediating process and stewardship of the local needs. Fourth, the HWSI can be replicable at various scales and contexts, which could be considered for further research. Finally, recognizing the local arrangements and building the capacity of water actors are of paramount importance.